Cultural turnover among Galápagos sperm whales. Issue 10 (October 2016) - Cantor, Mauricio; Whitehead, Hal; Gero, Shane; Rendell, Luke
Abstract : While populations may wax and wane, it is rare for an entire population to be replaced by a completely different set of individuals. We document the large-scale relocation of cultural groups of sperm whale off the Galápagos Islands, in which two sympatric vocal clans were entirely replaced by two different ones. Between 1985 and 1999, whales from two clans (called Regular and Plus-One ) defined by cultural dialects in coda vocalizations were repeatedly photo-identified off Galápagos. Their occurrence in the area declined through the 1990s; by 2000, none remained. We reassessed Galápagos sperm whales in 2013–2014, identifying 463 new females. However, re-sighting rates were low, with no matches with the Galápagos 1985–1999 population, suggesting an eastward shift to coastal areas. Their vocal repertoires matched those of two other clans (called Short and Four-Plus ) found across the Pacific but previously rare or absent around Galápagos. The mechanisms behind this cultural turnover may include large-scale environmental regime shifts favouring clan-specific foraging strategies, and a response to heavy whaling in the region involving redistribution of surviving whales into high-quality habitats. The fall and rise of sperm whale cultures off Galápagos reflect the structuring of the Pacific population into large, enduring clans with dynamic ranges. Long-lasting clan membership illustrates how culture can be bound up in the structure and dynamics of animal populations and so how tracking cultural traits can reveal large-scale population shifts.